Attentional Lapses in Attention-Deficit/Hyperactivity Disorder: Blank Rather Than Wandering Thoughts. (October 2017) - Van den Driessche, Charlotte; Bastian, Mikaël; Peyre, Hugo; Stordeur, Coline; Acquaviva, Éric; Bahadori, Sara; Delorme, Richard; Sackur, Jérôme
People with attention-deficit/hyperactivity disorder (ADHD) have difficulties sustaining their attention on external tasks. Such attentional lapses have often been characterized as the simple opposite of external sustained attention, but the different types of attentional lapses, and the subjective experiences to which they correspond, remain unspecified. In this study, we showed that unmedicated children (ages 6–12) with ADHD, when probed during a standard go/no-go task, reported more mind blanking (a mental state characterized by the absence of reportable content) than did control participants. This increase in mind blanking happened at the expense of both focused and wandering thoughts. We also found that methylphenidate reverted the level of mind blanking to baseline (i.e., the level of mind blanking reported by control children without ADHD). However, this restoration led to mind wandering more than to focused attention. In a second experiment, we extended these findings to adults who had subclinical ADHD. These results suggest that executive functions impaired in ADHD are required not only to sustain external attention but also to maintain an internal train of thought.